Monopodial and sympodial bamboos grown in tropic and sub-tropic countries – A Review - Hamid, Norul Hisham; Jawaid, Mohammad; Abdullah, Ummi Hani; Alomar, Taghrid S. (North Carolina State University, 2023)
Bamboo belongs to the grass family and is an important non-timber forest product in tropic and sub-tropic countries. The global trade of bamboo products is worth billions of dollars and is mainly dominant with monopodial bamboo grown in sub-tropic countries such as China and Japan. Many researchers globally discuss that in addition to species and region, bamboo quality can differ based on its rhizome types because the physiology is different for both monopodial and sympodial bamboo. However, there is a massive competition within the yearly forest products due to the challenges posed by underground root system in agroforestry. This review studied the properties of bamboo with regards to their differences in terms of monopodial and sympodial types of rhizomes. It was found that most of the structural, chemical organic, and mechanical properties are higher in monopodial bamboo, but there is a greater fibre morphology and decay resistance in the sympodial bamboo.